Etanercept in moderate rheumatoid arthritis: PRESERVE study results from central/eastern Europe, Latin America and Asia. (October 2014) - Pavelka, Karel; Burgos-Vargas, Ruben; Miranda, Pedro; Guzman, Renato; Yen, Jeng-Hsien; Izzi, Mustafa Al; Szekanecz, Zoltan; Tang, Boxiong; Szumski, Annette; Kotak, Sameer; Bananis, Eustratios; Koenig, Andrew S; et al.
Aims: We compared etanercept 50 mg once weekly (ETN50)/methotrexate versus etanercept 25 mg (ETN25)/methotrexate or biologic-free methotrexate after response to ETN50/methotrexate in moderate rheumatoid arthitis patients from central/eastern Europe, Latin America and Asia.Methods: In a 36-week induction phase, methotrexate-resistant patients received ETN50/methotrexate. In a 52-week, double-blind phase, patients who achieved sustained Disease Activity Score in 28 joints low disease activity (LDA) were randomized to ETN50/methotrexate, ETN25/methotrexate or methotrexate.Results: Sustained Disease Activity Score in 28 joints LDA was achieved in 85% at week 36. LDA was achieved in 83, 81 and 50% with ETN50/methotrexate, ETN25/methotrexate and methotrexate and remission in 66, 61 and 31%, respectively, at week 88 (p < 0.0001).Conclusion: Etanercept/methotrexate therapy for 36 weeks effectively induced response in this moderate rheumatoid arthritis subpopulation. Conventional- and reduced-dose etanercept/methotrexate was significantly more effective over the subsequent 52 weeks than biologic-free therapy.